Trends in the distribution of added value of listed industrial companies: 1990 to 2002 - N. Van Aswegen; B. W. Steyn; W. D. Hamman (South African Journal of Business Management, 2005)
Value added is a measure of the increase in wealth of a company. The question posed in this paper, is whether there was a change over time; firstly in the percentage of added value by companies as a proportion of sales and secondly in the distribution of the added value between the different stakeholder groups.The ratio VA/sales and the VA distribution ratios were calculated for three samples:A full sample from 1990 to 2002, consisting of all the listed South African companies preparing a value added statement; A constant sample of 36 companies that existed from 1990 to 2002; and A constant sample of 55 companies that existed from 1994 to 2002.Although a slight downward trend was found in VA/sales from 1997/1998, there is not enough evidence to infer that there was a change over time in VA/sales as the differences in the central location for at least two years were not significant.It was determined that there was only one distribution ratio in each constant sample with a significant difference in the central locations between at least two of the years. These ratios were retention/VA for the constant sample from 1990 to 2002 and depreciation/VA for the constant sample from 1994 to 2002.The change over time in depreciation was probably caused by the change in accounting treatment for amortisation of intangible assets. Retention is a balancing figure – the leftovers after the other allocations have been done – it can therefore be expected that this ratio will be influenced by the changes in all the other allocations. The general prosperity of the company and the economy will also influence retention, as the total value added will change accordingly and that will determine what is being left for retention in the company. As the growth in the GDP increased during the period under review, it was no surprise to find an increase in the ratio retention/VA.
Keywords: 650